Landscape connectivity loss after the de-escalation of armed conflict in the Colombian Amazon (2011–2021) (2024)
Rapid deforestation has been well-documented in Colombia after the 2016 peace agreement with FARC. While many analysis using remote sensing identify land cover change, structural connectivity variables are less studied for understanding landscape transformation. In this work, we used data from the Landsat archive from 2011 to 2021, the Continuous Change Detection and Classification algorithm (CCDC), and Morphological Spatial Pattern Analysis (MSPA) to analyze deforestation, land cover change, and landscape connectivity in northwestern Colombia's Amazon. We examined the spatial patterns in three specific subsets in the Colombian arc of deforestation, with a special focus on the surroundings of the National Natural Park Serranía de Chiribiquete. Our results confirm changes in structural connectivity linked to pasture expansion from the conversion forest to pasture during the analyzed period showing changes in the borders of Serranía de Chiribiquete National Park along rivers and roads, where cattle is transported. Before 2016, the average annual deforested area in the three study areas was 27.93 km²